Salmonella sp. and Escherichia coli Contamination on Cattle Beef from Binjai City Slaughterhouse and Tavip Market - Hasnudi; P. Patriani; M.I. Aja; Capah, S.M (Talenta Publisher, 2022)
Salmonella sp. and Escherichia coli became contaminator bacteria that influenced the microbiological quality of beef. Environmental conditions, facilities, and slaughterhouse infrastructure cause contamination. This study aimed to determine the presence of Salmonella sp. and Escherichia coli contamination on slaughtered beef from Binjai City slaughterhouse and Tavip Market. This study used a descriptive and purposive sampling technique and 12 samples (6 from the slaughterhouse and six from Tavip Market). This study was conducted at Binjai City Slaughterhouse and Tavip Market. It was analyzed at the Cell and Tissue Cultures Laboratory in the University of North Sumatera Faculty of Medicine in November 2021. Data analysis used Paired Sample T-Test. The result showed the absence of Salmonella sp. contamination on the Binjai City slaughterhouse and Tavip Market sample. Furthermore, all the samples were contaminated by Escherichia coli, and 5 out of 6 samples surpassed the SNI 3932:2008. This study concludes that the average of Escherichia coli in slaughterhouse samples differs significantly from the sample from Tavip Market.